INFLUENCE OF FINE ART ON HUMAN PSYCHOLOGY (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article is illustrative A lot of information about art and psychology is given. It is explained that the combination of visual arts and psychology is an effective means of supporting the mental and emotional health of a person and plays an important role in improving the quality of life.